Hand and Wrist: A Kaleidoscopic View of Accessory Ossicles, Variants, Coalitions, and Others - Mespreuve, Marc; Bosmans, Frederik; Waked, Karl; Vanhoenacker, Filip M. (Seminars in Musculoskeletal Radiology, 2019)
Accessory bones, variants, and coalitions are not uncommon at the hand-wrist region. They are often overlooked because they are usually asymptomatic and found incidentally on imaging. However, they may sometimes present as a (painful) swelling or mimic a (sequel of a) fracture. Other symptoms may be attributed to impingement and exercise-related pain. Thorough knowledge of the anatomy, systematic imaging analysis, and the awareness of their existence are the clues to a correct identification. Plain radiography and magnetic resonance imaging (MRI) play a pivotal role in the correct diagnosis. In general, signal intensity on MRI is similar to the normal bony structures. However, concomitant bone marrow edema may indicate the presence of impingement. Therefore, MRI sequences with fat suppression should be included in case of symptomatic findings. This article provides a kaleidoscopic overview of some of the prevalent bony anomalies of the hand-wrist region and their potential pathogenic nature.
Keywords: accessory bone; variants; coalitions; plain radiography; magnetic resonance imaging